IORT as adjuvant treatment in primary rectal carcinomas: multi-modality treatment - Eble, Michael J.; Lehnert, Thomas; Herfarth, Christian; Wannenmacher, Michael (Intraoperative radiation therapy in the treatment of cancer, 1997)
010122004 1997Copyright / Drug Dosage / DisclaimerCopyright: All rights reserved. No part of this publication may be translated into other languages, repro
Gesehen am 26.08.2025